The relationship between consumer buying behavior, social aspects, and technostress on smartphone - Hadi, Antonius Satria (Asian Management and Business Review, 2022)
The objectives of this study is to investigate the influence of social aspects including social need and social influence toward dependency, the influence of dependency toward repeat purchase intention and technostress. Respondents in this research were 200 undergraduate students from universities in Yogyakarta, Indonesia. This research has four hypotheses. The analytical technique used in this research were Confirmatory Factor Analysis (CFA) and Structural Equation Model (SEM) using LISREL 10 software. The results of this research empirically proves that social aspects including social need and social influence has significant and positive effect toward dependency, and dependency has significant and positive effect toward repeat purchase intention and technostress. Each of hypotheses were accepted and elaborated more detail in discussion section.